A frog thing - Drachman, Eric.; Muscarello, James (Los Angeles, CA : Kidwick Books, 2005)
Frank wasn$1 (Bt satisfied doing ordinary frog things. He wanted to fly, but he was a frog and frogs can$1 (Bt fly. Follow Frank as he jumps and runs and leaps and dives until he finally finds his place in the pond. .s
Keywords: Frogs -- Juvenile fiction; Self acceptance -- Juvenile fiction